Re-igniting awareness of local folklore through community engagement: A collaborative effort of USM, UiTM and WOU. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2011)
Traditionally, institutions of higher learning have always been seen as the source of new knowledge where solutions to complex problems are debated and unravelled. In response to the global trend where knowledge has become a commodity, higher education institutions are also evolving into a pre-eminent catalyst of societal change.